การพัฒนาคู่มือการสร้างรูบริคเพื่อให้คะแนนสำหรับการประเมินการปฏิบัติงานของผู้เรียน - นันทนัช อ่อนพวน (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The proposes of research were 1) to study the state of students’ performance assessment, creating and using scoring rubric for students’ performance assessment in basic education, 2) to study the problems of creating and using scoring rubric for students’ performance assessment in basic education, and 3) development of a handbook for creating scoring rubric for students’ performance assessment. This study was a research and development using 3 research methodologies. In survey research, participants were 356 teachers using multi-stage random sampling. Research instrument was questionnaire. In quantitative and qualitative study, participants were 5 experts. Research instruments were evaluation of a handbook and record the interview. Finally, in quasi-experiment, participants were 10 teachers using purposive sampling. Research instruments were testing, scoring rubric and evaluation of a handbook. Analyze data was used descriptive statistics, t-test and content analysis. The results were summarized as follows: 1. Most teachers in all learning strands made students’ performance assessment based on the state of assessment principles and evaluation, and they used scoring rubric for students’ performance assessment. 2. Teachers using scoring rubric for students’ performance assessment had problem in the time limitation of creating and using scoring rubric, the most. 3. The contents of a handbook for creating scoring rubric for students’ performance assessment included five chapters; 1) introduction 2) performance assessment 3) creating scoring rubric for performance assessment 4) validity and reliability and 5) using scoring rubric for performance assessment. The pretest score of teachers’ knowledge of scoring rubric between experimental group and control group were not statistically significantly different (p>.05), whereas the posttest score of teachers’ knowledge of scoring rubric of those groups were statistically significantly different (p<.05). In addition, the posttest score of teachers’ performance of scoring rubric between two groups were not statistically significantly different (p>.05).